(untitled) (Iranian Journal of Kidney Diseases, 2016)
Introduction. This study aimed to evaluate the prevalence of vitamin D inadequacy in patients receiving maintenance hemodialysis and peritoneal dialysis (PD) and its association with inflammatory and nutritional factors. Materials and Methods. A total of 176 hemodialysis and 32 PD patients participated in the study. Serum levels of 25-hydroxyvitamin D, albumin, parathyroid hormone, calcium, phosphorus, high-sensitivity C-reactive protein (HSCRP), and neutrophil-lymphocyte ratio (NLR) were measured. Data on body mass index were also collected. Stepwise multiple logistic regression analysis was used to identify predictors for 25-hydroxyvitamin D deficiency and its relationship with the nutritional and inflammatory factors. Results. No significant association was found between 25-hydroxyvitamin D and age, body mass index, serum calcium, serum phosphorus, parathyroid hormone, serum albumin, dialysis quality, and duration of dialysis; while NLR and HSCRP were significantly associated with 25-hydroxyvitamin D in the hemodialysis patients only (P < .001 and P = .001, respectively). A positive correlation was found between NLR and HSCRP in both hemodialysis and PD patients. (r = 0.817; P < .001). This association was confirmed between an NLR greater than 3 and an HSCRP level greater than 3. Conclusions. Vitamin D deficiency was highly prevalent in our dialysis patients, and inadequate level of vitamin D was associated with inflammatory factors such as HSCRP and NLR in both hemodialysis and PD patients. An easy and inexpensive test of an NLR greater than 3 could be used as a measure of inflammation instead of HSCRP in both PD and hemodialysis patients.